Hydrothermal waves of droplet evaporation - Ho, Ai Wei (2015)
The dynamic of evaporating droplets are vital to many biomedical, technological and natural applications that concern the idea of heat and mass transfer; this includes biological aspect of DNA mapping, biofluid analysis, technological aspect of printing, cooling of machines like nuclear plants and natural aspect of water cycle. The existence of hydrothermal waves is discovered decades ago, although much research is done, they ended up with trivial results as the use of infrared camera haven not been employed. Hence, it is worthwhile to investigate further using an infrared camera to observe the thermal patterns of the evaporating process of a fluid. This study would discusses the experimental results of evaporating ethanol, novec-7100 and deionized water. It aims to facilitate the understanding of the underlying factors affecting the thermal motion, pattern and direction of hydrothermal waves. Two sets of experiments, cone shaped and rectangular shaped containers heated at the edge, have been employed to achieve the aim of this study respectively. The first group of experiments showed that deionized water does not exhibit hydrothermal waves due to its capillary length greater than its droplet depth. This is supported by experiment that varies with supplied voltage. Under higher voltage thermal motion of deionized water remains calm and constant, but thermal motion, increase rapidly for ethanol and Novec-7100. Also, temperature field is plotted against normalized radial position and observation of evaporation occur mainly in the center, where deionized water showed otherwise. All these results are proven of the existence of hydrothermal waves during evaporation of ethanol and novec-7100 but not in deionized water. Lastly, the number of hydrothermal waves were found to vary exponentially with supplied voltage. In the second group of experiments, hydrothermal waves were also showed to exist in the rectangular base droplet. It has a constant propagating angle, perpendicular to heat source and these waves are stripe-like propagating from cold to hot region. As the above experiments are mostly targeted at pure volatile liquid, future works can be done to conduct studies on fluid that contains nanoparticle that will alter the thermal conductivity and hence the temperature gradient of the fluid.